SERUM CHLORIDE-TO-SODIUM RATIO AND OUTCOMES IN HYPONATRAEMIC ACUTE DECOMPENSATED HEART FAILURE: A PROSPECTIVE COHORT STUDY - Dr. Marinna Ponnachan; Dr. Anil Kumar; Dr. G B Doddamani; Dr. Santosh M Hegde (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Hyponatraemia frequently accompanies acute decompensated heart failure (ADHF) and portends poor outcome. Emerging data suggest that chloride—long overshadowed by sodium—may carry independent prognostic weight. We assessed whether the admission serum chloride-to-sodium ratio (Cl⁻/Na⁺) improves risk‐stratification in hyponatraemic ADHF. Methods: In this prospective cohort (January 2022–June 2024) we enrolled 302 consecutive adults (age 66 ± 12 years, 38 % women) hospitalised with ADHF and serum Na⁺ < 135 mmol L⁻¹. Baseline demographics, comorbidities, natriuretic peptides and full metabolic panels were recorded. The primary end-point was 180-day all-cause mortality; secondary end-points were in-hospital worsening HF and 30-day readmission. Patients were stratified by admission Cl⁻/Na⁺ tertiles (T1 ≤ 0.98, T2 0.99–1.03, T3 ≥ 1.04). Multivariable Cox and logistic models adjusted for age, sex, eGFR, LVEF, NT-proBNP and diuretic dose evaluated associations. Results: Mean admission Na⁺ was 129 ± 4 mmol L⁻¹ and Cl⁻/Na⁺ 1.01 ± 0.04. During follow-up, 71 deaths (23.5 %) occurred. Crude 180-day mortality rose step-wise across tertiles (T1 14 %, T2 21 %, T3 35 %; p < 0.001). Each 0.01-unit decrement in Cl⁻/Na⁺ conferred a 6 % relative risk reduction (adjusted HR 0.94, 95 % CI 0.90–0.99, p = 0.02). Adding Cl⁻/Na⁺ to a validated ADHF score improved C-statistic from 0.77 to 0.81 (p = 0.01) and yielded a net reclassification improvement of 0.18. Low Cl⁻/Na⁺ also independently predicted in-hospital worsening HF (OR 1.42 per 0.01-unit drop, p = 0.008) and 30-day readmission (OR 1.27, p = 0.04). Conclusion: Among hyponatraemic ADHF patients the admission Cl⁻/Na⁺ ratio is an easily obtainable, independent predictor of short- and medium-term outcomes and meaningfully enhances existing risk scores. Routine reporting and therapeutic trials targeting chloride homeostasis merit consideration.